2009
DOI: 10.1073/pnas.0909893106
|View full text |Cite
|
Sign up to set email alerts
|

Acidianus filamentous virus 1 coat proteins display a helical fold spanning the filamentous archaeal viruses lineage

Abstract: Acidianus filamentous virus 1 (AFV1), a member of the Lipothrixviridae family, infects the hyperthermophilic, acidophilic crenarchaeaon Acidianus hospitalis. The virion, covered with a lipidic outer shell, is 9,100-Å long and contains a 20.8-kb linear dsDNA genome. We have identified the two major coat proteins of the virion (MCPs; 132 and 140 amino acids). They bind DNA and form filaments when incubated with linear dsDNA. A C-terminal domain is identified in their crystal structure with a four-helix-bundle fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 44 publications
2
35
0
1
Order By: Relevance
“…Notably, both AFV1 MCPs possess a four-helix-bundle fold resembling that in the MCP of SIRV (SIRV-134), a finding not only in support of the recent grouping of the two viral families into the order Ligamenvirales but also suggestive of a possible similarity in the architectural roles of MCPs of the two viral families (69). Indeed, mixing of either of the two AFV1 MCPs with DNA fragments gave rise to long flexible filaments in vitro (123). Although these filaments are not directly relevant to virion structure, both proteins are likely involved in nucleocapsid assembly.…”
Section: Assembly and Releasesupporting
confidence: 49%
“…Notably, both AFV1 MCPs possess a four-helix-bundle fold resembling that in the MCP of SIRV (SIRV-134), a finding not only in support of the recent grouping of the two viral families into the order Ligamenvirales but also suggestive of a possible similarity in the architectural roles of MCPs of the two viral families (69). Indeed, mixing of either of the two AFV1 MCPs with DNA fragments gave rise to long flexible filaments in vitro (123). Although these filaments are not directly relevant to virion structure, both proteins are likely involved in nucleocapsid assembly.…”
Section: Assembly and Releasesupporting
confidence: 49%
“…7), suggesting that viruses from the two families descended from a common ancestor (202,214). This proposal has recently been strengthened by high-resolution structural analysis, which revealed that the DNA-binding major capsid proteins of rudiviruses and lipothrixviruses share the same fold (93,268). Interestingly, the fold of the major capsid protein is unique to these linear archaeal viruses and has not yet been observed for viruses from the other two domains of life (141).…”
Section: Vol 75 2011 Genomics Of Prokaryotic Viruses 623mentioning
confidence: 74%
“…The filamentous, enveloped virions of lipothrixviruses are composed of two MCPs, MCP1 and MCP2. The structures of both proteins from the virus AFV1 have been determined by X-ray crystallography [7], revealing the same unique four-helixbundle fold at the C-termini of both proteins (Fig. 3B).…”
mentioning
confidence: 99%
“…GenBank accession numbers: Rudiviridae MCPs (SIRV1 ORF134, NP_666607; SIRV2 ORF134, NP_666560; SRV ORF134, CAQ58456; ARV gp24, YP_001542641), Lipothrixviridae MCP1 (AFV1 ORF132, YP_003749; AFV3 gp34, YP_001604376; AFV6 gp35, YP_001604193; AFV7 gp28, YP_001604252; AFV8 gp30, YP_001604311; AFV9 gp32, YP_001798550; SIFV ORF35, NP_445700) and MCP2 (AFV1 ORF140, YP_003750; AFV3 gp35, YP_001604377; AFV6 gp36, YP_001604194; AFV7 gp29, YP_001604253; AFV8 gp31, YP_001604312; AFV9 gp33, YP_001798551; SIFV ORF36, NP_445701) (color figure online) Proposal for creation of the order ''Ligamenvirales '' 793 regions, the two AFV1 MCPs display a distinct hydrophobicity profile, which allowed the topological model to be proposed. According to this model, the basic MCP1 forms a core around which the genomic dsDNA is wrapped, whereas the MCP2 interacts with the genome with its basic N-terminal region, and the hydrophilic C-terminal domain is embedded in the lipid envelope [7]. The rodshaped, non-enveloped virions of rudiviruses are composed of one major protein: the highly basic MCP accounts for 99% of virion proteins and associates with the genomic DNA to form the helical body of the virion.…”
mentioning
confidence: 99%